Efficacy of local prostaglandin analogues for vitiligo treatment: a systematic review and meta-analysis. Issue 3 (4th March 2022) - Chang, Hua-Ching; Guo, Siao-Pei
ABSTRACT: Background: Vitiligo is a common cutaneous depigmentation disorder. Although multiple treatment options are available, no single modality is satisfactory for all patients. Several studies have demonstrated that prostaglandin analogues can potentially treat cutaneous depigmentation, but the evidence is limited to their inconsistent study design. Research design & methods: A systematic review was performed for studies published before 29 June 2021, in PubMed, Embase, Web of Science, or the Cochrane Library. The primary outcome of pooled analysis was the repigmentation efficacy of local prostaglandin analogues compared with other therapies for vitiligo. Results: Six randomized controlled trials (RCTs) and three non-RCTs were included in this systematic review, and seven studies among them were used for the meta-analysis. The pooled analysis demonstrated that local prostaglandin analogues could significantly increase repigmentation along with narrowband ultraviolet B phototherapy compared with phototherapy alone. Furthermore, the repigmentation efficacy of topical prostaglandin analogues was not significantly different from that of topical tacrolimus. In summary, local prostaglandin analogues either used alone or as add-on therapy could be safe and effective therapies for vitiligo.